Some Remarks on Spaces of Morrey Type - Loredana Caso; Roberta D'Ambrosio; Sara Monsurrò (Abstract and Applied Analysis)
We deepen the study of some Morrey type spaces, denoted by Mp,λ(Ω), defined on an unbounded open subset Ω of ℝn. In particular, we construct decompositions for functions belonging to two different subspaces of Mp,λ(Ω), which allow us to prove a compactness result for an operator in Sobolev spaces. We also introduce a weighted Morrey type space, settled between the above-mentioned subspaces.